Spatial orientation as a factor in flow boiling heat transfer of cooling liquids in enhanced surface minichannels. (February 2018) - Strąk, Kinga; Piasecka, Magdalena; Maciejewska, Beata
Highlights: Steady-state flow boiling heat transfer in a minichannel, asymmetrical heated. A rectangular minichannel, oriented with seven positions, several cooling liquids. Detection of temperature on the heated wall by infrared thermography. Using the Trefftz functions for determination of the heat transfer coefficient. Results: two-phase flow structures, the heat transfer coefficient, boiling curves. Abstract: This paper presents the results of flow boiling heat transfer in an asymmetrically heated rectangular minichannel oriented with seven inclination angles: 0°, 30°, 60°, 90°, 120°, 150°, and 180° relative to the horizontal plane. The liquid flowing in the minichannel, Fluorinert FC-72, HFE-7100 or HFE-7000 (3M), was heated by a thin plate. The plate had an enhanced surface on the side that was in contact with the fluid. The enhanced surface was obtained by vibration-assisted laser surface texturing. Infrared thermography was used to determine changes in the temperature on the outer smooth side of the plate. Two-phase flow patterns were observed through a glass panel. Local heat transfer coefficients between the heated plate and the cooling liquid flowing in a minichannel were calculated with the Trefftz method. The method approximates the unknown solution of differential equation by a linear combination of functions that exactly satisfy the differential equation. The results are presented as images of the two-phase flow structures, relationships between the temperature plate and the distance from the channel inlet, the heat transfer coefficient values and the distance from the channel inlet or the channel orientation and as boiling curves for selected working fluids and orientations of the test module. They are discussed separately for the subcooled and for the saturated boiling regions.